2010
DOI: 10.1016/j.jneumeth.2010.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Semi-automated Sholl analysis for quantifying changes in growth and differentiation of neurons and glia

Abstract: There is a need to develop therapies that promote growth or remyelination of mammalian CNS axons. Although the feasibility of pre-clinical treatment strategies should be tested in animal models, in vitro assays are usually faster and less expensive. As a result, in vitro models are ideal for screening large numbers of potential therapeutics prior to use in more complex in vivo systems. In 1953, Sholl introduced a technique that is a reliable and sensitive method for quantifying indices of neurite outgrowth. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 24 publications
2
59
0
Order By: Relevance
“…2C). To quantify the aggregate data, we determined the areas under curves in Figure 2C (Gensel et al 2010), and found that the area for apCRNF treatment was significantly larger than the area for the control treatment (two-tailed t-test, t (17) ¼ 2.214, P , 0.05) (Fig. 2D).…”
Section: Apcrnf Enhances Sn Neurite Growth and Branchingmentioning
confidence: 99%
See 1 more Smart Citation
“…2C). To quantify the aggregate data, we determined the areas under curves in Figure 2C (Gensel et al 2010), and found that the area for apCRNF treatment was significantly larger than the area for the control treatment (two-tailed t-test, t (17) ¼ 2.214, P , 0.05) (Fig. 2D).…”
Section: Apcrnf Enhances Sn Neurite Growth and Branchingmentioning
confidence: 99%
“…Recombinant apCRNF (250 ng/mL) or vehicle (0.1% BSA in PBS) was added on cultured SNs at Day 3 in vitro and incubated for 3 d. Bright field images were captured with a Zeiss Axiovert 200 microscope. Twenty evenly spaced concentric circles with increasing radii from 30 to 315 mm were overlaid onto the center of a cell soma; neurite elongation and branchings were measured by Sholl analysis (Sholl 1953;Gensel et al 2010). …”
Section: Structure-based Alignmentmentioning
confidence: 99%
“…After injury, CNS neurons fail to upregulate regeneration-associated genes (RAGs), those genes encoding proteins that promote cytoskeletal dynamics and growth-associated changes (Skene and Willard, 1981;Jacobson et al, 1986;Bonilla et al, 2002;Mason et al, 2002;Khazaei et al, 2014). Numerous neuron-extrinsic barriers also conspire to prevent efficient CNS growth and repair (McKeon et al, 1991;Brambilla et al, 2005;Donnelly and Popovich, 2008;Pineau et al, 2010;Alilain et al, 2011;Gaudet and Popovich, 2014). For example, inflammatory macrophages can cause axonal injury or inhibit axon regeneration after spinal cord injury (SCI) (Popovich et al, 1997;Kigerl et al, 2006;Kigerl et al, 2009;Prüss et al, 2011;Pool et al, 2012;Kroner et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas little is known about miR-155-3p, miR-155-5p has been studied extensively in inflammatory diseases and cancer. In the CNS, miR-155-5p can be found in microglia/macrophages (Tili et al, 2007;Cardoso et al, 2012), astrocytes (Tarassishin et al, 2011), and neurons (Herai et al, 2014). The therapeutic potential of targeting miR-155 is exemplified by the fact that miR-155 removal improves repair and recovery in other animal models of CNS pathology, including amyotrophic lateral sclerosis (Koval et al, 2013;Butovsky et al, 2015), multiple sclerosis , and central neuroinflammation (Lopez-Ramirez et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation